Integrating quantitative morphological and intratumoural textural characteristics in FDG-PET for the prediction of prognosis in pharynx squamous cell carcinoma patients. Issue 12 (December 2018) - Fujima, N.; Hirata, K.; Shiga, T.; Li, R.; Yasuda, K.; Onimaru, R.; Tsuchiya, K.; Kano, S.; Mizumachi, T.; Homma, A.; Kudo, K.; Shirato, H.
Abstract : Aim: To assess potential prognostic factors in pharynx squamous cell carcinoma (SCC) patients by quantitative morphological and intratumoural characteristics obtained by 2-[ 18 F]-fluoro-2-deoxy-d- glucose positron-emission tomography/computed tomography (FDG-PET/CT). Materials and methods: The cases of 54 patients with pharynx SCC who underwent chemoradiation therapy were analysed retrospectively. Using their FDG-PET data, the quantitative morphological and intratumoural characteristics of 14 parameters were calculated. The progression-free survival (PFS) and overall survival (OS) information was obtained from patient medical records. Univariate and multivariate analyses were performed to assess the 14 quantitative parameters as well as the T-stage, N-stage, and tumour location data for their relation to PFS and OS. When an independent predictor was suggested in the multivariate analysis, the parameter was further assessed using the Kaplan–Meier method. Results: In the assessment of PFS, the univariate and multivariate analyses indicated the following as independent predictors: the texture parameter of homogeneity and the morphological parameter of sphericity. In the Kaplan–Meier analysis, the PFS rate was significantly improved in the patients who had both a higher value of homogeneity ( p= 0.01) and a higher value of sphericity ( p= 0.002). With the combined use of homogeneity and sphericity, the patients with different PFS rates could be divided more clearly. Conclusion: The quantitative parameters of homogeneity and sphericity obtained by FDG-PET can be useful for the prediction of the PFS of pharynx SCC patients, especially when used in combination. Highlights: Semi-automated quantitative parameters from FDG-PET data were calculated. Quantitative parameters can predict progression free survival in pharynx SCC patients. Combination use of sphericity and homogeneity can be a powerful predictor.